Livestock Development Policies in Eastern and Southern Africa (1) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
The seminar focused on socio-economic, scientific and technical factors related to formulating livestock development policies. The themes covered include: marketing; interactions between livestock and crops, wildlife and the environment; and animal health